Developing therapeutically more efficient Neurturin variants for treatment of Parkinson's disease - Runeberg-Roos, Pia; Piccinini, Elisa; Penttinen, Anna-Maija; Mätlik, Kert; Heikkinen, Hanna; Kuure, Satu; Bespalov, Maxim M.; Peränen, Johan; Garea-Rodríguez, Enrique; Fuchs, Eberhard; Airavaara, Mikko; Kalkkinen, Nisse; et al. (Neurobiology of disease, 2016)
In Parkinson's disease midbrain dopaminergic neurons degenerate and die. Oral medications and deep brain stimulation can relieve the initial symptoms, but the disease continues to progress. Growth factors that might support the survival, enhance the activity, or even regenerate degenerating dopamine neurons have been tried with mixed results in patients. As growth factors do not pass the blood-brain barrier, they have to be delivered intracranially. Therefore their efficient diffusion in brain tissue is of crucial importance. To improve the diffusion of the growth factor neurturin (NRTN), we modified its capacity to attach to heparan sulfates in the extracellular matrix. We present four new, biologically fully active variants with reduced heparin binding. Two of these variants are more stable than WT NRTN in vitro and diffuse better in rat brains. We also show that one of the NRTN variants diffuses better than its close homolog GDNF in monkey brains. The variant with the highest stability and widest diffusion regenerates dopamine fibers and improves the conditions of rats in a 6-hydroxydopamine model of Parkinson's disease more potently than GDNF, which previously showed modest efficacy in clinical trials. The new NRTN variants may help solve the major problem of inadequate distribution of NRTN in human brain tissue. •We developed new NRTN variants for treatment of PD.•All new NRTN variants are biologically active.•Within the brain two of the new NRTN variants diffuse better than WT NRTN.•These two new NRTN variants are also more stable than WT NRTN.•One of the new NRTN variants is more efficient than GDNF in a rodent model of PD.